The Contributions of Selected Women Occupational Groups to Rural Development in Ejigbo and Ife Central Local Government Areas in Osun State, Nigeria - Fagbewesa, Esther Olapeju (2015)
The study identified women occupational groups involved in rural development in Ife Central and Ejigbo Local Government Areas, and examined their organisational structure and mode of operations. It also assessed the contributions of the women occupational groups in promoting rural development. This was with a view to identifying the problems confronting and inhibiting these groups in demonstrating their full potentials in rural development.